2017
DOI: 10.1002/col.22182
|View full text |Cite
|
Sign up to set email alerts
|

Application of the nondestructive second derivative spectrophotometry to eliminate the effect of substrate in identification of madder used in Persian carpets

Abstract: The handmade Persian carpet is famous worldwide not only for its elegant design and artistic structure, but also for its brilliant color harmony and incomparable raw materials. Various natural dyes accompanied by different mordants are used on various woolen yarns to obtain a wide range of unrepeatable shades for carpet. In this article, as a first step, the diversity of the undyed woolen yarns used in Persian carpets was statistically investigated by implementation of the Principle Component Analysis. Then th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Color strengths ( K / S ) of the dyed samples were calculated using the Kubelka–Munk function as shown in eq K / S = false( 1 R false) 2 / 2 R where K is the absorption coefficient, S is the light scattering coefficient, and R is the observed reflectance. Generally, the higher the K / S value, the higher the depth of the color on the fabric. , …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Color strengths ( K / S ) of the dyed samples were calculated using the Kubelka–Munk function as shown in eq K / S = false( 1 R false) 2 / 2 R where K is the absorption coefficient, S is the light scattering coefficient, and R is the observed reflectance. Generally, the higher the K / S value, the higher the depth of the color on the fabric. , …”
Section: Methodsmentioning
confidence: 99%
“…Generally, the higher the K/S value, the higher the depth of the color on the fabric. 54,55 Fastness Test. The wash fastness test of dyed fabrics with PLTbased supramolecular salts was executed by a soaping machine (SW-24E) according to the standard test method ISO 105-B02.…”
Section: H 22 No 4 ]•[C 7 H 6 No 3 ]mentioning
confidence: 99%
“…Equations ( 1) and (2) were also used to calculate the color strength (k/s) of colored wools. The absorption coefficient is k, the light scattering coefficient is S and the reflection measured by the spectrophotometer is R (Ghanean and Ghanbar Afjeh, 2016). In the experimental design, the sum of k/s was determined and used as the color strength and responsiveness (Burkinshaw, 2016).…”
Section: Color Characteristics Of Dyed Samplesmentioning
confidence: 99%
“…Abu used the single constant KM theory for the hyperspectral images of 'Selden Map of China', transformed the reflectance into absorption and scattering ratio (K/S), and then used the non-negative constrained least squares method to achieve the pigment abundance calculated [10]. Sarvenaz et al used a combination of single constant KM theory and second derivatives to find the abundance of each component dye of the mixed dye color, and finally compared with the real data and found that they were able to accurately estimate the abundance [11]. With the development of deep learning, Rohani N combined single constant KM theory and deep neural networks to achieve the solution of pigment abundance, and found that the proposed algorithm of reconstructing the error of different colors can accurately estimate the pigment abundance effectively [12].…”
Section: Introductionmentioning
confidence: 99%